Overview of OxLDL and Its Impact on Cardiovascular Health: Focus on Atherosclerosis - Poznyak, Anastasia V.; Nikiforov, Nikita G.; Markin, Alexander M.; Kashirskikh, Dmitry A.; Myasoedova, Veronika A.; Gerasimova, Elena V.; Orekhov, Alexander N. (Frontiers in Pharmacology, 2021)
Cardiovascular pathologies maintain the leading position in mortality worldwide. Atherosclerosis is a chronic disease that can result in a variety of serious complications, such as myocardial infarction, stroke, and cardiovascular disease. Inflammation and lipid metabolism alterations play a crucial role in atherogenesis, but the details of relationships and causality of these fundamental processes remain not clear. The oxidation of LDL was considered the main atherogenic modification of LDL within the vascular wall for decades. However, recent investigations provided a growing body of evidence in support of the multiple LDL modification theory. It suggests that LDL particles undergo numerous modifications that change their size, density, and chemical properties within the blood flow and vascular wall. Oxidation is the last stage in this cascade resulting in the atherogenic properties. Moreover, recent investigations have discovered that oxLDL may have both anti-inflammatory and pro-inflammatory properties. Oxidized LDL can trigger inflammation through the activation of macrophages and other cells. After all, oxidized LDL is still a promising object for further investigations that have the potential to clarify the unknown parts of the atherogenic process. In this review, we discuss the role of oxLDL in atherosclerosis development on different levels.